2014
DOI: 10.1016/j.mexoft.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of keratoconus in an adolescent population

Abstract: Introduction: Keratoconus is an idiopathic and progressive disease, where the cornea develops an irregular and conical shape, being the most common form of dystrophy or corneal ectasia, developing between the age of 12 and 20. In Mexico, the epidemiological information about the pathology is scarce. Purpose: To explore the epidemiology of keratoconus in Mexico among adolescents, and to compare the prevalence with international literature reports. This study identified associated pathologies and examined the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 9 publications
4
28
1
2
Order By: Relevance
“…Our study showed that the mean age of patients with keratoconus was (24.9 ± 7.9), which is comparable with the results of other studies as those done in Asia by Saini G et al [33], they found the mean age of patients was (21.3±6.96), study done by Pearson AR, Soneji B, Sarvananthan N, et al [34] on white patients, showed that the mean age was (26.5 ± 8.5 years) and a study done in Mexican by Aníbal Cruz-Becerril et al [35] reported that the mean age was (28.14±10.30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that the mean age of patients with keratoconus was (24.9 ± 7.9), which is comparable with the results of other studies as those done in Asia by Saini G et al [33], they found the mean age of patients was (21.3±6.96), study done by Pearson AR, Soneji B, Sarvananthan N, et al [34] on white patients, showed that the mean age was (26.5 ± 8.5 years) and a study done in Mexican by Aníbal Cruz-Becerril et al [35] reported that the mean age was (28.14±10.30).…”
Section: Discussionsupporting
confidence: 92%
“…The patient eyes develop different variants of astigmatism especially myopic astigmatism. As the corneal curvature increased, the degree of astigmatism also increases causing a reduction in visual acuity of patient's eyes [33]. There are few relevant studies on other refractive errors that can be found in keratoconus, which we try, to asses in our study.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, a higher mean age, around 27 years, was detected in Caucasian populations, suggesting a later disease onset [ 16 ], which is also seen in Macedonia, as the mean age at the time of disease detection was 26.81 ± 1.25 [ 17 ]. In general, our results agreed with those of internationally published studies concerning the early age of onset [ 18 ]. Several possible reasons could be cited here to explain these differences, including genetics and environmental and geographical factors, such as consanguineous marriages and ultraviolet exposure, which are considered the main risk factors for KC development and thus may explain the much earlier age of onset in the Saudi Arabian study compared with other studies.…”
Section: Discussionsupporting
confidence: 91%
“…5 Algunos autores plantean que es más frecuente en el sexo femenino y en edades comprendidas entre los 30 y 39 años, aunque otros reportan a la población masculina como más afectada y en edades entre los 24 y 30 años, siendo controversial la relación de la enfermedad y el sexo. 3,12 Actualmente es considerada una enfermedad rara con muy baja incidencia en la población, su diagnóstico no es difícil en grados avanzados no así en aquellas personas en que la enfermedad es incipiente y donde apenas hay signos o manifestaciones clínicas. En estos casos se requiere de la combinación de medios diagnósticos que ayuden a corroborar el diagnóstico clínico para un mejor tratamiento.…”
Section: El Queratocono Concepción Origen Y Epidemiologíaunclassified
“…Otro aspecto que otorga notabilidad al estudio del tema es la insuficiente información epidemiológica sobre el comportamiento de algunas variables de la población afectada considerando las condiciones del hábitat o zona geográfica donde vive, el tipo de nutrición o estado nutricional, las características étnicas, consanguineidad, entre otras que pudieran aportar información valiosa para un mejor diagnóstico, manejo o tratamiento y prevención de la afección. 7 Resulta importante el estudio del tema considerando que desde el punto de vista ético algunas alternativas de tratamiento quirúrgico utilizan tejido de humanos o de potenciales donantes de órganos, para reemplazo de las córneas en personas enfermas con queratocono. Estas personas requieren de la sustitución cuando con los tratamientos de menor complejidad no lograron corrección o mejoría de la agudeza visual.…”
Section: Introductionunclassified